Analysis of Talent Management, Career Development, and Knowledge Management on Employee Performance : Literature Review - Zulfikar, Muhammad Vicky (IJBLE Scientific Publications Community Inc., 2024)
In the intense international competition environment, companies need to improve their performance with the quality and knowledge of human resources. However, talent management, professional development and knowledge management are often poorly managed in organizations, especially government institutions, where they are not organized through success and work. The research used is a qualitative method and data analysis by collecting data from sources such as management books, research articles and documents such as GARUDA, Google Scholar, ScienceDirect, ResearchGate, Tandfonline and Scopus. The results of the literature review show that talent management includes the activities of identifying, selecting, developing and retaining talents according to their qualities in order to achieve the company's goals. While career development helps employees develop their interests, needs and career choices, knowledge management aims to develop the skills and abilities of employees.